Comparative survey of the six-minute walk test on the treadmill and on the corridor in cardiac patients - Benedita Kamily Oliveira Magalhães; Caio César Guimarães de Freitas; Natália Bitar da Cunha Olegario; Framartinho Carlos Silva Araújo; Guilherme Pinheiro Ferreira da Silva
Introduction The six minute walk test (6MWT) is considered an important tool in the evaluation of physical capacity, monitoration and the effectiveness of treatment in cardiac patients.Objective To compare the 6MWT on the treadmill and corridor in cardiac patients.Methods Participated 24 cardiac patients, being 12 male and 12 female with 56.7 ± 12.7 years age average, submitted to the six-minute walk test on the treadmill (6MWTT) and on the corridor (6MWTC) in an interval of seven days. The analyzed variables were: walked distance, respiratory rate (RR), heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP) and oxygen saturation (SatO2).Results It was statistically significant difference in the comparison between the tests for the variables: walked distance, SBP, DBP and SatO2 (p > 0.05). The only statistically significant variable was the HR after the test application (p = 0.03).Conclusion After the two tests application, there was similarity in the variables: walked distance, SBP, DBP and SatO2 with no significant statistical differences. Only the HR presented statistical significance between groups at the end of the tests.